Case Report: Behçet’s syndrome and venous thrombosis in children: a case study and review of the literature - Yin, Qinan; Bian, Yuan; Niu, Fang; Zhang, Mao; Chen, Siyu (Frontiers in Immunology, 2025)
Venous thromboembolism (VTE) is an exceedingly rare occurrence in pediatric patients with Behçet’s syndrome (BS). Currently, the clinical anticoagulation treatment regimen for this condition in the pediatric population remains inadequately defined. Here, we reported the treatment process of a child with Behçet’s disease complicated by VTE and reviewed the relevant literature to study comprehensive diagnosis and treatment strategies, as well as the latest progress for this specific type of disease. A 15-year-old boy who presented BS with pulmonary embolism, pulmonary aortic aneurysm, and recurrent deep vein thrombosis was described. Following a comprehensive strategy of systematic immunotherapy and anticoagulation treatment, the patient’s condition has shown significant improvement, with marked relief from pulmonary embolism and lower extremity venous thrombosis. In addition to the systematic immunotherapy, anticoagulant therapy plays a significant role in the diagnosis and treatment of these patients. The literature review shows that 16 of the 17 patients underwent heparin anticoagulant therapy, while 6 were additionally treated with vitamin K antagonists (VKs). Our case study also indicated that vitamin K antagonists can be applied in this population. Moreover, it is imperative to conduct extensive long-term follow-up studies to better evaluate the outcomes of anticoagulation therapy as these patients transition into adulthood.